Engineered nanoparticles and organic matter: a review of the state-of-the-art - Grillo, Renato [UNESP]; Rosa, Andre H. [UNESP]; Fraceto, Leonardo F. [UNESP] (Elsevier B.V., 2015)
Growth in the development and production of engineered nanoparticles (ENPs) in recent years has increased the potential for interactions of these nanomaterials with aquatic and terrestrial environments. Carefully designed studies are therefore required in order to understand the fate, transport, stability, and toxicity of nanoparticles. Natural organic matter (NOM), such as the humic substances found in water, sediment, and soil, is one of the substances capable of interacting with ENPs. This review presents the findings of studies of the interaction of ENPs and NOM, and the possible effects on nanoparticle stability and the toxicity of these materials in the environment. In addition, ENPs and NOM are utilized for many different purposes, including the removal of metals and organic compounds from effluents, and the development of new electronic sensors and other devices for the detection of active substances. Discussion is therefore provided of some of the ways in which NOM can be used in the production of nanoparticles. Although there has been an increase in the number of studies in this area, further progress is needed to improve understanding of the dynamic interactions between ENPs and NOM. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Nanoparticles; Natural organic matter; Humic/fulvic substances; Nanotoxicology